THE MAGELANG POLICE DRUGS UNIT INVESTIGATION EFFORTS IN INCREASING DISCLOSURE OF CRIMINAL ACTS OF DRUGS ABUSE - MUHAMMAD YUZAKKY MUHAMMAD YUZAKKY (Advances in Police Science Research Journal, 2022)
Drug abuse is stated in Law Number 35 of 2009 concerning Narcotics That importing, exporting, producing, planting, storing, distributing, and/or using Narcotics without strict and thorough control and supervision is contrary to the laws and regulations and is a criminal act This is because drugs have a very detrimental impact and are a very big danger to human life, society, nation and state as well as Indonesia's national security. Technological advances also support criminals to profit through illegal trade. Transactions through Instagram social media and using online shopping, the convenience of this illicit transaction is carried out easily only by using a mobile phone. Perpetrators also have more varied motives, so it is necessary to increase investigation efforts so that they can reveal cases of drug abuse with a complex modus operandi. This study is intended to find out the investigation efforts carried out in increasing the disclosure of criminal cases of drug abuse by describing the implementation of investigations carried out by the Narcotics Unit in revealing cases of drug abuse in the Magelang Police area. The approach used in this study is a qualitative approach with a combination of observation techniques or observations and interviews, and participation through document examination. as an analytical knife to describe the implementation of drug abuse investigations by the Magelang Police Drug Unit